Mimicry and Resistance in Tere Liye's Anak Nusantara Novel Series - Setiowati, Eva; Subyantoro, Subyantoro; Setyaningsih, Nas Haryati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The practice of colonialism still exists today. It looks at literary works, like the novel series Anak Nusantara. This research aims to analyze the forms of mimicry and resistance in the novel series Anak Nusantara. This research uses a postcolonialism approach. The data in this study consists of text quotations in the form of sentence fragments that show mimicry and resistance. The data source in this study is the novel series Anak Nusantara by Tere Liye. It consists of five (5) novels: Si Anak Kuat (2018) has 397 pages; Si Anak Spesial (2018) has 333 pages; Si Anak Pintar (2018) has 349 pages; Si Anak Pemberani (2018) has 424 pages; and Si Anak Cahaya (2018) has 421 pages. The five novels are recovered from the novel series Anak Mamak published by Republika. The results show the existence of mimicry and resistance. The form of mimicry in the novel is shown in the form of behavior, the use of transportation, language, and buildings. The form of resistance is shown in the form of passive resistance and radical resistance.